الآثار الاجتماعية، الاقتصادية والمكانية لوباء COVID 19 في تركيا: Social, economic, and spatial impacts of COVID-19 pandemic in Turkey - بوخبزة فوزية, (Journal of North African Economies, 2025)
This article aims to study the social, economic and spatial impacts of the COVID-19 pandemic and the variously affected economic sectors in Turkey and highlights the factors that distinguish Turkey from other countries with a special focus on the factors affecting the spread of the epidemic, and the determinants of the changes caused by the epidemic in mobility between individuals. This study reveals the factors that distinguish Turkey from other countries and highlights the various challenges it faced, as the impacts of COVID-19 in Turkey also differ from several international perspectives compared to other countries and regionally through different social, economic and regional dynamics within the country. From an international perspective, the most prominent factor that distinguishes Turkey from other countries is its effective economic performance during the pandemic, as it was considered among the few countries with positive performance and its experience is one of the most successful in the world.